1995
DOI: 10.1142/s0217979295001464
|View full text |Cite
|
Sign up to set email alerts
|

THE INFLUENCE OF SINTERING AND Sb CONTENT ON THE FORMATION OF HIGH TEMPERATURE SUPERCONDUCTING PHASE IN Bi(Pb)-Sr-Ca-Cu-O SYSTEM

Abstract: Six different compositions in ( Bi 1.5 Pb 0.5−x Sb x) Sr 2 Ca 2 Cu 3 O y (with x = 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5) have been prepared by the solid state reaction method. Sintering at different temperatures (between 800–860° C) and time periods has been carried out in order to study its effect on T c values. The samples have been characterized by x ray powder diffraction (XRD), Scanning Electron Microscopy (SEM) and measurement of resistance at various temperatures. The study reveals that the incorporation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The addition of such a small proportion of Sb helps in increasing the high T c 2223 phase in the product when sintered for 643 hours at 860 • C and using a slow cooling procedure. From the present study and also from our previous investigations on the Bi-Pb-Sb-Sr-Ca-Cu-O system, [18][19][20] it may be concluded that the addition of a small amount of Sb, say 5%, to the Bi 1.5 Pb 0.5 Sb 2 Ca 2 Cu 3 O y is beneficial to obtain a high proportion of high T c 2223 phase. Simultaneous replacement of Bi by Pb and Sb normally results in a multiphase product.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The addition of such a small proportion of Sb helps in increasing the high T c 2223 phase in the product when sintered for 643 hours at 860 • C and using a slow cooling procedure. From the present study and also from our previous investigations on the Bi-Pb-Sb-Sr-Ca-Cu-O system, [18][19][20] it may be concluded that the addition of a small amount of Sb, say 5%, to the Bi 1.5 Pb 0.5 Sb 2 Ca 2 Cu 3 O y is beneficial to obtain a high proportion of high T c 2223 phase. Simultaneous replacement of Bi by Pb and Sb normally results in a multiphase product.…”
Section: Discussionsupporting
confidence: 77%
“…Some of these results of this study have been reported elsewhere. [18][19][20] We have also observed that Sb content, annealing time and temperature all affect the quality of the high T c superconductivity phase. In the present study, we have synthesized a composition of Bi 1.5 Pb 0.5 Sr 2 Ca 2 Cu 3 O y with an addition of 5% Sb using the solidstate reaction method.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the high-Tc phase the highest intensity peak for the sample (A1) was found to be 735 counts per second (CPS) at 2θ value of 30 • and for sample (A2), the highest intensity peak was obtained at 859 CPS at 2θ value of 28 Figs. 1-3 show that a sharp and intense peak corresponding to the high-Tc (2 2 2 3) phase [10,23], appearing at low 2θ value of nearly 5 • , gradually increases in its intensity with increase in antimony content from x = 0.02 to 0.08 and the maximum intensity of 647 CPS was obtained for this peak at 2θ value of 4.72 • for the sample (A5) having x = 0.08. However, on further increase in antimony content such as x = 0.15 for sample (A6) as shown in Fig.…”
Section: Resultsmentioning
confidence: 95%